Marketing a felsőoktatásban: Weboldalak elemzési szempontrendszere a magyar és nemzetközi szakirodalom alapján - Misley, Helga; Vámos, Ágnes (Magyar Pedagógia, 2017)
Information on higher education institutions today is primarily sought online. University and college websites are not only sources of information; they are also means of self-presentation and marketing communication. Their structure and tone determine what users think of an institution (Middleton, McConnell and Davidson, 1998; Kent and Taylor, 2002; McAllisterSpooner, 2009). The link between higher education institutions and their users is an opportunity for these institutions and a basic requirement from the perspective of website users. The purpose of our literature review is to explore the dominant approaches and methods of international and domestic research on website analysis focused on higher education institutions. The multiple foci of the research are reflected in the fact that researchers on the subject have evaluated web pages based on different units, thus creating a variety of models, sets of criteria, and schemas. After reviewing the research, based on the most important evaluation criteria for web pages, we have created a market-based system of criteria – credibility, interactivity, content, information, attractiveness, and design – integrated with the Conceptual Framework of University Website Quality (WEBQUAL) set up by Khawaja and Bokhari (2010). We have summarized this in a model of marketing elements on educational institution websites. Based on a review of topic-specific research trends, it is possible to determine whether the interface that a visitor encounters promotes or hampers (a) the „sale” of a product, such as training, on the supply side and (b) its „purchase” on the demand side. The way this complex system is built, how well it performs and is managed, and how adaptive it is to internal and external changes may make the institution attractive and inspire prospective students, proving that it is both good and worthy of being associated with this community.